2019
DOI: 10.1029/2019gl082086
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Ensemble Simulations of Intense Tropical Cyclones and Their Internal Variability During the El Niños of 1997 and 2015

Abstract: Extreme El Niño events affect the number of intense tropical cyclones (ITCs) over the western North Pacific (WNP). In 1997 and 2015, both extreme El Niño years, ITC numbers were above normal in the WNP. In order to clarify how, and to what extent, sea surface temperature anomaly (SSTA) distributions control the ITCs genesis, the authors conducted 50‐member ensemble simulations using a high‐resolution global nonhydrostatic model that explicitly simulates ITCs. The ensemble simulations showed a clear relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Additionally, some recent studies found that anomalous subtropical NP warming was responsible for the failure in seasonal forecasting of the 2016 WNP TC season following the 2015–2016 El Niño event (Chen & Wang, ; C. Wang, Wu, et al, ; Y.‐K. Wu et al, ; Yamada et al, ; Zhan et al, ). Specifically, the WNP usually experiences an inactive TC season following a strong El Niño event due to the existence of an anomalous anti‐cyclonic circulation, which is coupled to the underlying SST cooling in the NP (B. Wang et al, ; B. Wang & Chan, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Additionally, some recent studies found that anomalous subtropical NP warming was responsible for the failure in seasonal forecasting of the 2016 WNP TC season following the 2015–2016 El Niño event (Chen & Wang, ; C. Wang, Wu, et al, ; Y.‐K. Wu et al, ; Yamada et al, ; Zhan et al, ). Specifically, the WNP usually experiences an inactive TC season following a strong El Niño event due to the existence of an anomalous anti‐cyclonic circulation, which is coupled to the underlying SST cooling in the NP (B. Wang et al, ; B. Wang & Chan, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The second model was the 60‐km‐mesh Meteorological Research Institute (MRI) Atmospheric General Circulation Model (MRI‐AGCM), version 3.2 (Mizuta et al, ; Murakami, Mizuta, et al, ; Murakami, Wang, et al, ; Yoshida et al, ), which was developed by the Japan Meteorological Agency and MRI. The third model was the 14‐km‐mesh Nonhydrostatic Icosahedral Atmospheric Model (NICAM) developed at the Japan Agency for Marine‐Earth Science and Technology, University of Tokyo, and Riken (Miura et al, ; Nakano et al, ; Satoh et al, ; Satoh et al, ; Yamada et al, ; Yamada et al, ), which configures a global cloud‐resolving model and adopts nonhydrostatic governing equations and icosahedral grids. Some of the experiments were not conducted with NICAM (supporting information Table S1) owing to limited computational resources.…”
Section: Datamentioning
confidence: 99%
“…On interannual time scales, the frequency of WNP TCs can be modulated by various climate factors such as the El Niño/La Niña Modoki 1,2 , the Pacific Meridional Mode (PMM) [3][4][5][6] , the Atlantic Meridional Mode 7 , tropical North Atlantic (TNA) sea surface temperature (SST) [8][9][10] , Indian Ocean SST [11][12][13][14] , and SST gradient between the southwestern Pacific Ocean and the western Pacific warm pool 15 . A more recent study has further pointed out that regional SST anomalies (SSTA) can modulate TC genesis in different parts of the WNP 16 .…”
mentioning
confidence: 99%